Propuesta para la creación de la casa de la cultura del Choco. - Ortiz Santos, Esperanza (Universidad Antonio Nariño, 2021)
In Colombia, the state promotes and fosters cultural access, through scientific, artistic, technical, empirical and professional education, the Ministry of Culture provides it with funds for the promotion and dissemination of the country's cultural heritage. In the department of Chocó, young people and the community in general need cultural, educational, and sports settings, where the population can enjoy healthy and suitable environments for the development of cultural, artistic, scientific, and economic activities that are visualized and promoted. territorial development; The creation of a house of culture in Chocó will be very important because it will allow ancestral knowledge to be passed on to new generations, which will allow them to be taken into account and viewed as an endogenous factor of cultural development and social transformation from the territory.